Ozone stress in woody plants assessed with chlorophyll a fluorescence. A critical reassessment of existing data - Bussotti, Filippo; Desotgiu, Rosanna; Cascio, Chiara; Pollastrini, Martina; Gravano, Elisabetta; Gerosa, Giacomo; Marzuoli, Riccardo; Nali, Cristina; Lorenzini, Giacomo; Salvatori, Elisabetta; Manes, Fausto; Schaub, Marcus; et al. (Environmental and Experimental Botany, 2011)
This paper proposes an overall reassessment of results from ﬂuorescence transient (FT) and modulated ﬂuorescence (MF) analysis on tree species subjected to treatment with ozone. Findings from literature and open-top chamber experiments were used in this review, in order to identify damage mechanisms and repair/avoidance strategies. Main results are summarised below. (i) The most widely used parameter to assess the response to ozone treatment was the quantum yield of primary photochemistry in the dark-adapted state (ϕPo, or FV/FM). This parameter proved to be very stable in stress and control conditions. Ozone-induced stress – and the related loss of photosynthetic efﬁciency and performance – was characterized by the change occurring in all parameters connected with the controlled dissipation: reduction of FM, FV/FM, RC/CS0 (in the ﬂuorescence transient analysis) and NPQ (in theMF analysis). This can be considered as a down-regulationmechanism aimed at lowering the electron supply as a consequence of a reduced demand from the Calvin cycle. (ii) The FT analysis revealed a change in the I–P region shape, indicating that events beyond PSI are affected. These events include a lesser density of PSI itself and the compromised ability of the end acceptors of electrons (ferredoxine, NADP + ) and RuBP to manage effectively the ﬂux of electrons. This behaviour may create an imbalance between electrons sent by the electron transport chain and those reaching the acceptors beyond PSI. Free electrons (those coming from PSI, but that do not reach the end acceptors) can activate the oxygen from fundamental to excited status, with production of ROS (Reactive Oxygen Species), thus inducing photo-oxidation processes of the cellular content. (iii) In many cases a temporarily enhanced efﬁciency of electron trapping and transport (expressed by the parameters FV/FM, ET/TR, PIABS, pQ) in PSII system has been observed. That efﬁciency has been connected to the triggering of repair processes, but when it is connected to a reduced end acceptor capacity in combination with reduced Calvin cycle energy demand lead to over-excitation of the photosynthetic apparatus and initiates response towards visible foliar injury. (iv) The behaviour of F0 can help us distinguish between different response strategies. The increase of F0 observed in some ozone-treated plant species is considered an expression of irreversible damage in PSII, whereas lowered values of this parameter may indicate the activation of PSII in the cells surrounding the damaged one, as part of a compensative process. Future directions for the research in this ﬁeld concern: (i) the possibility to combine ﬂuorescence parameters with carbon assimilation and growth to support the study on critical levels and (ii) the analysis of the events concerning the activity of PSI and the events leading to the ﬁxation of CO2, by using innovative technologies
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Chlorophyll a fluorescence; OKJIP transient; Open top chambers; Ozone stress; Performance index; Quantum yield efficiency; Reaction centres; Visible foliar symptoms